2018
DOI: 10.1177/1357633x18806651
|View full text |Cite
|
Sign up to set email alerts
|

Using telehealth to improve access to hepatitis C treatment in the direct-acting antiviral therapy era

Abstract: Introduction One-third of the Australian population lives outside major cities and this group has worse health outcomes. Telehealth is becoming an accepted way to improve patient access to specialist healthcare. Over 200,000 Australian’s have hepatitis C virus (HCV) and new treatments are very effective and well tolerated. We aim to demonstrate that HCV treatment utilising telehealth support for care delivery has cure rates similar to onsite care in clinical trials. We also report length of consultation and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…We included data from 16 selected studies that have utilized telehealth as an innovative mode of communication for the management of hepatitis C virus patients. Out of sixteen studies, ten studies were retrospective cohort studies [13][14][15]19,20,22,23,26,28,29], three were prospective cohort studies [18,24,30], one was a mixed methods study (both qualitative and quantitative components) [21] and the remaining two were observationaldescriptive studies [25,27]. The final selected studies were divided into four main categories which included improving treatment rates via utilizing telehealth services, satisfaction with telehealth services, disease management and health promotion, and similarity between telehealth and traditional modalities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included data from 16 selected studies that have utilized telehealth as an innovative mode of communication for the management of hepatitis C virus patients. Out of sixteen studies, ten studies were retrospective cohort studies [13][14][15]19,20,22,23,26,28,29], three were prospective cohort studies [18,24,30], one was a mixed methods study (both qualitative and quantitative components) [21] and the remaining two were observationaldescriptive studies [25,27]. The final selected studies were divided into four main categories which included improving treatment rates via utilizing telehealth services, satisfaction with telehealth services, disease management and health promotion, and similarity between telehealth and traditional modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Later, a single study was found from cross-referencing which was also included. As a result of the whole screening process, we included 16 studies for the purpose of this review as per our pre-defined eligibility criteria [13][14][15][18][19][20][21][22][23][24][25][26][27][28][29][30]. The entire process of study screening and selection is exemplified in the PRISMA flow diagram in Figure 1.…”
Section: Screening and Selection Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing point-of-care testing using HCV core antigen would reduce loss-to-follow-up and increase the engagement of PWIDs into HCV care [ 59 , 60 , 61 , 62 ]. Efficient testing can also be employed using novel methods/technologies, such as the mobile health vans program (A-CHESS), which allows for the implementation of several services and the collection of longitudinal data related to drug use and HCV care among people with opioid use disorders [ 63 ], and telehealth, which is cost-effective, saves time, and facilitates outreach/access to HCV treatment [ 64 ].…”
Section: Intervention Strategies For the Mena Regionmentioning
confidence: 99%